2019
DOI: 10.3390/ijerph16244914
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is Too Much? The Influence of Work Hours on Social Development: An Empirical Analysis for OECD Countries

Abstract: Work is a cornerstone of social development. Quantifying the impact on development of fluctuations in work hours is important because longer work hours increasingly seem to be the norm. Based on an integrative perspective that combines individual, organizational, and social factors, we constructed a model using data from 31 member countries of the Organisation for Economic Co-operation and Development (OECD). The proposed model was used to test the effect of work hours on different levels and to propose feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The empirical results are in line with other studies from the literature, which acknowledge the positive influence of household income [8], employment of young people [37] and working hours [38]. At the same time, OECD countries registered a different result: as the number of working hours increases, the rate of economic growth decreases [39].…”
Section: Discussionsupporting
confidence: 88%
“…The empirical results are in line with other studies from the literature, which acknowledge the positive influence of household income [8], employment of young people [37] and working hours [38]. At the same time, OECD countries registered a different result: as the number of working hours increases, the rate of economic growth decreases [39].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, it can also be observed that the reduction rate of the survival function decreases with the increasing level of urbanization, indicating that citizens in highly urbanized areas tend to work longer than those who live in non-urban areas. This finding is as expected because the increasingly competitive environment in urban areas puts many people under great pressure and, consequently, they need to work hard for a better quality of life [74,75].…”
Section: Results Of Survival Curve Analysissupporting
confidence: 68%
“…This means that the increase of weariness is not rewarded with matching resource, which can easily result in declining work performance or even turnover behaviors of employees. 3 Evidence has also been found that overtime behaviors can influence employees' individual health, family ties, emotional exhaustion, etc. 4,5 Overtime behaviors driven by involution will not only cause the loss of efficient employees, but also result in employees' losses more than their profits.…”
Section: Introductionmentioning
confidence: 99%